Is a sedentary lifestyle associated with a decrease in semen quality in adult men aged 18-50 years? A Systematic Review - Rizky Febriansyah; Bangar Parlinggoman Tua; Mutia Juliana; Aditya Rifandi Zaenudin (The Indonesian Journal of General Medicine, 2026)
Introduction: Global declines in semen quality over recent decades have raised concerns about the impact of modern lifestyles on male fertility. Sedentary behavior, increasingly prevalent in occupational and leisure settings, has been hypothesized as a potential contributing factor. This systematic review aims to evaluate whether a sedentary lifestyle is associated with decreased semen quality in healthy adult men aged 18-50 years. Methods: A systematic review was conducted following predefined screening criteria. Sixteen studies were included randomized controlled trial, etc. Studies were required to assess sedentary behavior (directly or indirectly), evaluate semen quality parameters (concentration, motility, morphology, volume, DNA fragmentation), and include healthy adult men aged 18-50 years. Data were extracted on study characteristics, sedentary behavior definitions, semen parameters, association findings, confounding factors, and limitations. Results: Direct evidence from two studies specifically measuring sedentary behavior showed inconsistent findings. Sterpi et al. (2024) reported mixed results across 13,509 men: three studies found declines in sperm concentration with high sedentary time, but most studies showed no significant associations with concentration, motility, or morphology. Eisenberg et al. (2015) found no association between occupational prolonged sitting and any semen parameter after adjustment for confounders. Indirect evidence from physical activity studies suggested that moderate physical activity benefits semen quality, while intense exercise may be detrimental (Montano et al., 2021; Nesello et al., 2020; Zańko et al., 2022). Obesity, strongly correlated with sedentary behavior, consistently predicted impaired semen quality (Magoutas et al., 2025; Venishetty et al., 2024; Бобков et al., 2020). Discussion: The available evidence does not demonstrate a robust independent association between sedentary behavior and decreased semen quality. Methodological limitations include heterogeneous definitions of sedentary behavior, reliance on self-report measures, inadequate adjustment for confounders (particularly BMI/obesity), and selection bias across study populations. The pathway linking sedentary behavior to semen quality appears mediated primarily through metabolic consequences (obesity, hormonal imbalances) rather than direct effects. Conclusion: Current evidence is insufficient to establish a causal relationship between sedentary lifestyle and decreased semen quality in healthy adult men aged 18-50 years. High-quality prospective studies using objective sedentary behavior measures (accelerometry) with adequate adjustment for adiposity and confounders are needed. Future research should distinguish between sedentary behavior's independent effects and those mediated through obesity.